Pembentukan Karakter Mulia Pada Anak Usia Dasar Berdasarkan Ajaran Kitab Ayyuhal Walad: Analisis Pemikiran Pendidikan Al-Ghazali - Malahayaty Tanjung; Mesran Mesran (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to analyze the formation of noble character among elementary school-aged children based on Imam Al-Ghazali's teachings in Ayyuhal Walad, focusing on character values, character formation methods, and their relevance to character education in the contemporary era. This study employs a qualitative approach using library research. Data were collected through documentation techniques from primary sources, particularly Ayyuhal Walad, and secondary sources consisting of relevant books and journal articles. Data were analyzed using content analysis through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that noble character in Al-Ghazali's thought encompasses an orientation toward beneficial activities, a balance between knowledge and practice, devotion in worship, sincerity, self-reflection, humility, and openness to receiving advice. Character formation is achieved through tazkiyatun nafs, habituation, exemplary conduct, and gradual education (tadarruj). These ideas remain relevant as a foundation for character education among elementary school-aged children in addressing the challenges of the digital era and globalization.